First mitochondrial genome of the Egyptian mongoose Herpestes ichneumon (Carnivora, Herpestidae). Issue 2 (1st February 2021) - Boukhdoud, Liliane; Parker, Lillian D; McInerney, Nancy Rotzel; Saliba, Carole; Kahale, Rhea; Maldonado, Jesús E; Bou Dagher Kharrat, Magda
Abstract: The Egyptian mongoose, Herpestes ichneumon, is the only extant mongoose in Europe, with populations still distributed in Africa and the Middle East. In this study, we present the first mitochondrial genome sequence of Herpestes ichneumon and we investigate its phylogenetic position within Feliformia suborder. The resultant mitogenome sequence is 16, 775 bps, composed of a conserved set of 37 genes containing 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. Our results represent a valuable resource for further phylogeographical studies.